Hubungan Minat Berwirausaha dengan Teaching Factory Siswa Kelas XI Kuliner di SMK Negeri 1 Ampek Angkek - Rahma Arifna; Ezi Anggraini; Elida Elida; Juliana Siregar (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Entrepreneurial interest has become one way to overcome the low number of entrepreneurs, especially among vocational school graduates. In this study, the entrepreneurial interest of eleventh-grade culinary students at SMK 1 Ampek Angkek will be explained, the teaching factory in the Creative Project and Entrepreneurship subject will be described, and the relationship between entrepreneurial interest and the teaching factory in the Creative Project and Entrepreneurship subject will be investigated. This type of study uses correlational methodology and is quantitative in nature. 54 students from the XI Culinary Department of SMK 1 Ampek Angkek constitute the population in this study. The sampling method used is total sampling, also known as census sampling. A Likert scale that has been tested for validity and reliability is used in the direct distribution of questionnaires for data collection. Descriptive analysis and correlation analysis are applied in data analysis. According to research, 35% of culinary students in the XI grade at SMK Negeri 1 Ampek Angkek have a moderate interest in starting their own business. With a ratio of 65%, the learning factory in the subjects of Creative Projects and Entrepreneurship is classified as average. The findings indicate that among culinary students in the XI grade at SMK 1 Ampek Angkek, there is a good and significant correlation between the teaching methods in the subjects of Creative Projects and Entrepreneurship and the students' interest in entrepreneurship.